2021
DOI: 10.1002/hon.2904
|View full text |Cite
|
Sign up to set email alerts
|

CD38 expression is an important prognostic marker in diffuse large B‐cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous group of diseases with variable outcomes. Although several prognostic markers have been developed, specific biomarkers for stratifying treatment strategies have not been fully investigated. This study aimed to analyze the clinical impact of the expression of cluster of differentiation (CD) 38, which is associated with cellular proliferation and disease progression, in patients with de-novo DLBCL. Using flow cytometry analysis, 137 cases with DLBCL were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Studies using flow cytometry have shown the association of the intensity of CD38 expression with more aggressive DLBCL variants or high CD38 expression to be an independent predictor of poor outcomes in de novo DLBCL. 21,22 This case could not be categorised into known variants of CD20 negative DLBCL and in the literature there are few reports describing such new cases of DLBCL, 20,23,24 Nakatsuka et al reported an EBV-positive DLBCL case that was negative for various B-cell (CD19, CD20, CD79a, CD38, CD138) and T-cell (CD3, CD4, CD5, CD8) markers. 20 This case was positive only for Oct-2 and BOB-1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using flow cytometry have shown the association of the intensity of CD38 expression with more aggressive DLBCL variants or high CD38 expression to be an independent predictor of poor outcomes in de novo DLBCL. 21,22 This case could not be categorised into known variants of CD20 negative DLBCL and in the literature there are few reports describing such new cases of DLBCL, 20,23,24 Nakatsuka et al reported an EBV-positive DLBCL case that was negative for various B-cell (CD19, CD20, CD79a, CD38, CD138) and T-cell (CD3, CD4, CD5, CD8) markers. 20 This case was positive only for Oct-2 and BOB-1.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular note, CD38 is highly expressed in two naïve B cell subsets that are only enriched in DHL patients. As a type II transmembrane glycoprotein, the highly expressed CD38 is an important factor in the poor prognosis of B cell lymphoma [ 32 , 33 ]. This suggests that CD38 could be a biomarker for diagnosis (distinguishing from other DLBCL subtypes) or prognosis of DHL.…”
Section: Discussionmentioning
confidence: 99%
“…CD38 expression is abnormally high in DLBCL and can be detected in 80% of the cases [ 22 ]. Expression of CD38 on the surface appears to correlate with aggressiveness of the tumor and, in de novo DLBCL, high CD38 expression is associated with significantly worse progression-free survival and poor overall survival [ 13 , 76 ]. There have been no oncogenic mechanisms directly attributed to CD38 in DLBCL so far; however, its expression on aggressive variants of DLBCL suggests that it may support a proliferative phenotype.…”
Section: Cd38-mediated Tumor-promoting Mechanisms and Expression In H...mentioning
confidence: 99%
“…Enhanced expression of the CD38 membrane protein has also been reported in other aggressive hematological malignancies, including chronic lymphocytic leukemia (CLL), T-cell acute lymphoblastic leukemia (T-ALL), diffuse large B-cell lymphomas (DLBCL), and T and NK lymphomas (NKTL) [ 13 , 14 , 15 , 16 , 17 ]. This elevated CD38 expression has been associated with poorer prognosis and a more aggressive cancer phenotype, which is an outcome of the cancer cell hijacking underlying CD38-driven functions to create both a pro-tumoral extracellular environment and a cancer-permissive intracellular milieu [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%